2017
DOI: 10.1627/jpi.60.26
|View full text |Cite
|
Sign up to set email alerts
|

Development of Predictive Methods of Water–Heavy Oil Phase Equilibrium for Supercritical Water Upgrading Process

Abstract: Predictive methodology was developed for water-hydrocarbon systems under high temperature and pressure conditions based on reported phase equilibrium data using the Peng-Robinson equation of state (EOS) for vaporliquid equilibrium (VLE) and liquid-liquid equilibrium (LLE). The available experimental data for hydrocarbons with low molecular weight and interaction parameter, kij, with/without a size parameter, lij, included in the PengRobinson EOS were fitted to experimental data and accumulated for constructing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For the mixture of heavy oil and SC benzene, a single-phase structure can always be maintained despite the difference in the thermodynamic state of benzene. As for the mixture of heavy oil and SC H 2 O following the type IIIb or type II phase behavior defined by van Konynenburg and Scottis, its phase structure is determined simultaneously by the thermodynamic state of water and the operating condition applied. A condensed oil-in-water emulsion structure could be formed at a low water density, a low water-to-oil ratio, or a low temperature. , At that time, light fractions are extracted into SC H 2 O, leaving heavy fractions concentrated in oil droplets. Driven by the attractive electrostatic interaction between oil fractions and SC H 2 O, the majority of heavy oil fractions tend to dissolve into SC H 2 O along with the increase in water density or temperature.…”
Section: Resultsmentioning
confidence: 99%
“…For the mixture of heavy oil and SC benzene, a single-phase structure can always be maintained despite the difference in the thermodynamic state of benzene. As for the mixture of heavy oil and SC H 2 O following the type IIIb or type II phase behavior defined by van Konynenburg and Scottis, its phase structure is determined simultaneously by the thermodynamic state of water and the operating condition applied. A condensed oil-in-water emulsion structure could be formed at a low water density, a low water-to-oil ratio, or a low temperature. , At that time, light fractions are extracted into SC H 2 O, leaving heavy fractions concentrated in oil droplets. Driven by the attractive electrostatic interaction between oil fractions and SC H 2 O, the majority of heavy oil fractions tend to dissolve into SC H 2 O along with the increase in water density or temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Water has a critical temperature of 647 K and a critical pressure of 22.1 MPa. Since the 1990s, the introduction of environmentally friendly supercritical water (SCW) in the upgrading of heavy oil has caused widespread concern in the academic community. Depending on the mutual solubility between the oil fraction and SCW, the mixture of heavy oil and SCW can exhibit type II or IIIb phase behavior as classified by van Konynenburg and Scott. Based on the experimental characterization on heavy oil pyrolysis in SCW, various phase structures such as two-phase, oil-in-water emulsion, and pseudo-single-phase structures were further suggested. …”
Section: Introductionmentioning
confidence: 99%
“…To quantitatively describe the phase behavior of heavy oil and water mixtures, Teratani et al tried to develop a predicative methodology based on the Peng–Robinson (PR) equation of state (EOS) . It was reported that the interaction parameters between water and hydrocarbons are independent of the size of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%